FGFR1-5-HT1A Heteroreceptor Complexes: Implications for Understanding and Treating Major Depression - Borroto-Escuela, Dasiel O.; Tarakanov, Alexander O.; Fuxe, Kjell (Elsevier, 2016)
The serotonin and neurotrophic factor hypotheses of depression are well known. The discovery of brain fibroblast growth factor receptor 1 (FGFR1)-5 hydroxytryptamine receptor 1A (5-HT1A) heteroreceptor complexes, and their enhancement of neuroplasticity, offers an integration of these hypotheses at the molecular level. They were first described in the hippocampus and later in midbrain 5-HT neurons, where these heterocomplexes are enriched in 5-HT1A autoreceptors. Combined FGF2 and 5-HT1A agonist treatment increased the formation of these heterocomplexes and the facilitatory allosteric receptor-receptor interactions within them led to the enhancement of FGFR1 signaling and was associated with the development of antidepressant effects. We discuss these findings with regard to a theory of motifs critically involved in these interactions and suggest that these complexes represent novel targets for antidepressants. 5-HT1A receptor is a 5-HT receptor subtype, which binds the endogenous transmitter 5-hydroxytryptamine. In the brain it participates in mediating antidepressant effects of classical antidepressant drugs and of serotonin selective reuptake inhibitors.FGFR1 is a receptor tyrosine kinase, the ligands of which are specific members of the fibroblast growth factor family. One of its ligands, FGF2, is shown to produce antidepressant-like effects.FGFR1-5-HT1A heteroreceptor complexes were recently discovered in the brain. In these heterocomplexes, agonist coactivation markedly enhanced FGFR1 signaling leading to increased neuroplasticity and antidepressant-like actions.The FGFR1-5-HT1A heteroreceptor complex represents a new promising target for antidepressant drugs including combined treatment with FGF2 and 5-HT1A agonists in major depression.
Keywords: Receptores de neurotransmisores; Depresión; Fibroblast growth factor receptor 1; 5-HT1A receptor; Heteroreceptor complexes; Allosteric receptor–receptor interactions; Depression; Neural plasticity